Feasibility, reproducibility and accuracy of electrical velocimetry for cardiac output assessment in congenital heart disease - Alexander C. Egbe; Muhammad Wajih Ullah; Arslan Afzal; Keerthana Banala; Rahul Vojjini; Maria Najam; Karim Osman; Sahith Thotamgari; Donald J. Hagler (International Journal of Cardiology: Heart & Vasculature, 2020)
Background: Noninvasive cardiac output assessment is important for prognostication in patients with heart failure. Electrical velocimetry (EV), an impedance cardiography technique, can be used for noninvasive cardiac output assessment. The purpose of this study was to determine the feasibility, reproducibility and accuracy of cardiac output assessment by EV in adults with congenital heart disease (CHD). Methods: Cross-sectional study of CHD patients that had simultaneous cardiac output assessment by Fick and EV (using Cardiotronic monitor, Osypka Medical). We divided the cohort into: Group 1 patients (n = 54) had hemodynamic assessment at rest only, while Group 2 patients (n = 7) had assessment both at rest and peak exercise. Results: EV cardiac output assessment was feasible in 100% of the patients. There was good correlation between Fick-derived and EV-derived cardiac index (r = 0.89, p < 0.001) in Group 1. Among 26 patients in Group 1 that underwent cardiac output assessment pre- and post-intervention, there was no difference in the strength of correlation of Fick and EV cardiac output pre- and post-intervention (p-interaction 0.244) indicating good reproducibility of the technique. There was also modest correlation between Fick-derived and EV-derived cardiac index at rest (r = 0.68, p = 0.032), and peak exercise (r = 0.62, p = 0.055), in Group 2. Conclusion: In this study, we demonstrated the feasibility and accuracy of EV cardiac output assessment in adults with CHD. We also demonstrated, for the first time, that EV cardiac output assessment was reproducible under different loading conditions, and that EV can be used for the assessment of cardiac output augmentation at peak exercise. Keywords: Cardiac output, Noninvasive hemodynamics, Congenital heart disease, Electrical velocimetry, Impedance cardiography